Gospodarka oparta na twórczości i jej pomiar - Wołoszyn, Jan (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
This article presents the basic concepts of creativity-based economy (GOT) by R. Florida and its method of measurement. The economy of creativity was shown in the context of a knowledge economy (GOW) showing their common and different issues. Measurement of GOT were related to three areas, namely talent, technology and tolerance. Place of Poland in the ranking of European countries, America and Asia in terms of ratio GOT and GOW was also presented. By showing the measurement procedure GOT one has also referred to the research of the conditions and quality of life of the Poles, in which, inter alia, the level of human capital, professed values or tolerance of the population were determined.